DEVELOPMENT OF SIRIH KUNING DANCE LEARNING VIDEO THROUGH CINEMATOGRAPHY TECHNIQUES FOR JUNIOR HIGH SCHOOL STUDENTS - Azella Ghaisani Amboro; Dwi Kusumawardani; Kartika Mutiara Sari (Universitas Pendidikan Indonesia, 2023)
This study aims to describe the process and results of the development of Sirih Kuning dance learning videos through cinematography techniques that can be applied in high school learning in learning Sirih Kuning dance. The underlying reason for this research is to provide learning solutions by producing learning videos of Sirih Kuning dance to help students learn on their own. This research uses the RD (Research and Development) method or is often referred to as research and development. The research process is carried out through the stages of analysis, development, implementation, and evaluation. The research found that the better the quality of dance learning videos used by students, the better the student learning outcomes. The research in the main is the feasibility test results obtained an average score from material experts (4. 66), from media experts (4.16) and from learning experts (4.6) getting a good category from the aspects of quality, benefits, suitability to the learning context. The effectiveness of the results show that the use of dance learning videos with cinematographic techniques can improve the learning outcomes of Sirih Kuning dance and make it easier to learn independently.